The Possible Role of Stem Cells in Acupuncture Treatment for Neurodegenerative Diseases: A Literature Review of Basic Studies. Issue 4 (May 2014) - Ho, Tsung-Jung; Chan, Tzu-Min; Ho, Li-Ing; Lai, Ching-Yuan; Lin, Chia-Hsien; Macdonald, Iona; Harn, Horng-Jyh; Lin, Jaung-Geng; Lin, Shinn-Zong; Chen, Yi-Hung
This review reports on recent findings concerning the effects of acupuncture and electroacupuncture (EA) on stem cell mobilization and differentiation, in particular with regard to neurogenesis. Traditional Chinese acupuncture has a history of over 2, 500 years and is becoming more popular worldwide. Evidence has demonstrated that acupuncture may be of benefit in stroke rehabilitation, parkinsonism, dementia, and depression. This article reviews recent studies concerning the effects of acupuncture/EA on stem cell mobilization and on progenitor cell proliferation in the CNS. The reviewed evidence indicates that acupuncture/EA has beneficial effects in several neurodegenerative diseases, and it may prove to be a nondrug method for mobilizing stem cells in the CNS.